Cordyceps acid alleviates lung cancer in nude mice. Issue 3 (30th November 2020) - Wang, Jing; Chen, Hongling; Li, Wanrong; Shan, Lingling
Abstract: The aim of this study is to examine the effect of cordyceps acid (CA) on lung cancer in mice. A lung cancer animal model was established by inoculating lung cancer cells under the armpit of nude mice. The mental state, body weight, and tumor growth of nude mice were recorded in detail. The levels of Nrf‐2/HO‐1/NLRP3/NF‐κB pathway and apoptosis in tumor tissues of nude mice were detected by the Western blot analysis and immunohistochemical methods. Our results show that CA inhibited lung cancer by regulating the Nrf‐2/HO‐1/NLRP3/NF‐κB signal. In summary, CA has an obvious tumor inhibiting effect on lung cancer via regulation of the Nrf‐2/HO‐1/NLRP3/NF‐κB signal.